Cross-metathesis reaction of α- and β-vinyl C-glycosides with alkenes - Šnajdr, Ivan; Parkan, Kamil; Hessler, Filip; Kotora, Martin (Beilstein Journal of Organic Chemistry, 2015)
Cross-metathesis of α- and β-vinyl C-deoxyribosides and α-vinyl C-galactoside with various terminal alkenes under different conditions was studied. The cross-metathesis of the former proceeded with good yields of the corresponding products in ClCH2CH2Cl the latter required the presence of CuI in CH2Cl2 to achieve good yields of the products. A simple method for the preparation of α- and β-vinyl C-deoxyribosides was also developed. In addition, feasibility of deprotection and further transformations were briefly explored.
Keywords: C-glycosides; catalysis; carbohydrates; cross-metathesis; ruthenium

(untitled) - Teo, Y. N.; Wilson, J. N.; Kool, E. T. (J. Am. Chem. Soc., 2009)

(untitled) - Wamhoff, H.; Warnecke, H. (ARKIVOC, 2001)

(untitled) - Novák, P.; Číhalová, S.; Otmar, M.; Hocek, M.; Kotora, M. (Tetrahedron, 2008)

(untitled) - Novák, P.; Pour, M.; Špulák, M.; Votruba, I.; Kotora, M. (Synthesis, 2008)

(untitled) - Bobula, T.; Hocek, M.; Kotora, M. (Tetrahedron, 2010)

(untitled) - Nečas, D.; Hidasová, D.; Hocek, M.; Kotora, M. (Org. Biomol. Chem., 2011)

(untitled) - Šnajdr, I.; Janoušek, Z.; Takagaki, M.; Císařová, I.; Hosmane, N. S.; Kotora, M. (Eur. J. Med. Chem., 2014)

(untitled) - Hessler, F.; Kulhavá, L.; Císařová, I.; Otmar, M.; Kotora, M. (Synth. Commun., 2014)

(untitled) - Takase, M.; Morikawa, T.; Abe, H.; Inouye, M. (Org. Lett., 2003)

(untitled) - Adamo, M. F. A.; Pergoli, R. (Org. Lett., 2007)

(untitled) - Heinrich, D.; Wagner, T.; Diederichsen, U. (Org. Lett., 2007)

(untitled) - Nakahara, M.; Kuboyama, T.; Izawa, A.; Hari, Y.; Imanishi, T.; Obika, S. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Kaliappan, K. P.; Kalanidhi, P.; Mahapatra, S. (Synlett, 2009)

(untitled) - Egron, D.; Durand, T.; Roland, A.; Vidal, J.-P.; Rossi, J.-C. (Synlett, 1999)

(untitled) - Jeanmart, S.; Taylor, R. J. K. (Tetrahedron Lett., 2005)

(untitled) - Rothman, J. H. (J. Org. Chem., 2009)

(untitled) - Aljarilla, A.; López, J. C.; Plumet, J. (Eur. J. Org. Chem., 2010)

(untitled) - Martin, A. R.; Mohanan, K.; Luvino, D.; Floquet, N.; Baraguey, C.; Smietana, M.; Vasseur, J.-J. (Org. Biomol. Chem., 2009)

(untitled) - Tietze, L. F.; Griesbach, U.; Schubert, I.; Bothe, U.; Marra, A.; Dondonni, A. (Chem. – Eur. J., 2003)

(untitled) - Wei, X.; Carroll, P. J.; Sneddon, L. G. (Organometallics, 2006)

(untitled) - Eignerová, B.; Janoušek, Z.; Dračínský, M.; Kotora, M. (Synlett, 2010)

(untitled) - Sedlák, D.; Eignerová, B.; Dračínský, M.; Janoušek, Z.; Bartůněk, P.; Kotora, M. (J. Organomet. Chem., 2013)

(untitled) - Rost, D.; Porta, M.; Gessler, S.; Blechert, S. (Tetrahedron Lett., 2008)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Samojłowicz, C.; Bienek, M.; Zarecki, A.; Kadyrov, R.; Grela, K. (Chem. Commun., 2008)

(untitled) - Samojłowicz, C.; Borré, E.; Maudit, M.; Grela, K. (Adv. Synth. Catal., 2011)

(untitled) - Samojłowicz, C.; Bienik, M.; Pazio, A.; Makal, A.; Woźniak, K.; Poater, A.; Cavallo, L.; Wójcik, J.; Zdanowski, K.; Grela, K. (Chem. – Eur. J., 2011)

(untitled) - Bargiggia, F. C.; Murray, W. V. (J. Org. Chem., 2005)

(untitled) - Michaut, A.; Boddaert, T.; Coquerel, Y.; Rodriguez, J. (Synthesis, 2007)

(untitled) - Prchalová, E.; Votruba, I.; Kotora, M. (J. Fluorine Chem., 2012)

(untitled) - Eignerová, B.; Dračínský, M.; Kotora, M. (Eur. J. Org. Chem., 2008)

(untitled) - Eignerová, B.; Slavíková, B.; Buděšínský, M.; Dračínský, M.; Klepetářová, B.; Šťastná, E.; Kotora, M. (J. Med. Chem., 2009)

(untitled) - Eignerova, B.; Sedlák, D.; Dračínský, M.; Bartůněk, P.; Kotora, M. (J. Med. Chem., 2010)

(untitled) - Řezanka, M.; Eignerová, B.; Jindřich, J.; Kotora, M. (Eur. J. Org. Chem., 2010)

(untitled) - Prchalová, E.; Štěpánek, O.; Smrček, S.; Kotora, M. (Future Med. Chem., 2014)

(untitled) - Dondoni, A.; Giovannini, P. P.; Marra, A. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Postema, M. H. D.; Piper, J. L. (Tetrahedron Lett., 2002)

(untitled) - Dominique, R.; Das, S. K.; Liu, B.; Nahra, J.; Schmor, B.; Gan, Z.; Roy, R. (Methods Enzymol., 2003)

(untitled) - Nolen, N. G.; Kurish, A. J.; Wong, K. A.; Orlando, M. D. (Tetrahedron Lett., 2003)

(untitled) - Lin, Y. A.; Chalker, J. M.; Davis, B. G. (J. Am. Chem. Soc., 2010)

(untitled) - Chen, G.; Schmieg, J.; Tsuji, M.; Franck, R. W. (Org. Lett., 2004)

(untitled) - Štěpánek, P.; Vích, O.; Werner, L.; Kniežo, L.; Dvořákova, H.; Vojtíšek, P. (Collect. Czech. Chem. Commun., 2005)

(untitled) - Liu, S.; Ben, R. N. (Org. Lett., 2005)

(untitled) - Voigtritter, K.; Ghorai, S.; Lipshutz, B. H. (J. Org. Chem., 2011)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)